Water vapour in the UTLS –Climatologies and Transport - Neis, Patrick (Forschungszentrum Jülich GmbH Zentralbibliothek, Verlag, 2017)
The knowledge about the water vapour distribution in the upper troposphere and lower stratosphere is essentialfor understanding the cloud formation processes and the Earth’s radiation budget. Since 1994, theEuropean infrastructure MOZAIC (since 2011 IAGOS) measures water vapour, temperature as well as differentessential climate variables, such as ozone and carbon monoxide (since 2001), aboard commercial passenger aircraft. Before analysing this more than two-decades comprehensive data set, the MOZAIC capacitive hygrometer is evaluated in a blind intercomparison against high precision water vapour instruments with the resulting sensors uncertainty of 5% relative humidity. To assure the data quality and the consistency of the data set, the new and improved IAGOS capacitive hygrometer is also evaluated against high precision water vapour instruments in a subsequent blind intecomparison. The water vapour data set is analysed with high vertical resolution around the thermal tropopause in the North Atlantic flight corridor and shows an increased probability of ice supersaturation with decreasing distance to the tropopause. This probability is especially pronounced in winter, but partially underestimated in its quantity in global weather models. Further analyses show a quasi-isentropic troposphere-to-stratosphere transport of water vapour near 50$^{°}$N and below 350 K of potential temperature in summer. Within a final case study the future potential of the IAGOS data set is demonstrated by using the new cloud index besides the simultaneous water vapour measurements to separate the water vapour distributions into clear sky and in-ice cloud data. With this separation, investigations show different amounts of cloud occurrence and cloud properties for different global regions.